Dealing With Unexpected Events on the Flight Deck: A Conceptual Model of Startle and Surprise. (December 2017) - Landman, Annemarie; Groen, Eric L.; van Paassen, M. M. (René); Bronkhorst, Adelbert W.; Mulder, Max
Objective: A conceptual model is proposed in order to explain pilot performance in surprising and startling situations. Background: Today's debate around loss of control following in-flight events and the implementation of upset prevention and recovery training has highlighted the importance of pilots' ability to deal with unexpected events. Unexpected events, such as technical malfunctions or automation surprises, potentially induce a "startle factor" that may significantly impair performance. Method: Literature on surprise, startle, resilience, and decision making is reviewed, and findings are combined into a conceptual model. A number of recent flight incident and accident cases are then used to illustrate elements of the model. Results: Pilot perception and actions are conceptualized as being guided by "frames, " or mental knowledge structures that were previously learned. Performance issues in unexpected situations can often be traced back to insufficient adaptation of one's frame to the situation. It is argued that such sensemaking or reframing processes are especially vulnerable to issues caused by startle or acute stress. Conclusion: Interventions should focus on (a) increasing the supply and quality of pilot frames (e.g., though practicing a variety of situations), (b) increasing pilot reframing skills (e.g., through the use of unpredictability in training scenarios), and (c) improving pilot metacognitive skills, so that inappropriate automatic responses to startle and surprise can be avoided. Application: The model can be used to explain pilot behavior in accident cases, to design experiments and training simulations, to teach pilots metacognitive skills, and to identify intervention methods.